Preparation and application of Joule thermal synthesis graphene and lithium iron phosphate composite material
The preparation of graphene and lithium iron phosphate composite materials through Joule thermal synthesis technology has solved the problems of low energy density, insufficient endurance and poor low-temperature performance of lithium iron phosphate batteries, and achieved performance improvement and cost reduction.
Patent Information
- Application Number
- CN202411815268.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing lithium iron phosphate batteries have low energy density, insufficient battery life compared with ternary lithium batteries, and poor low temperature performance, and higher production costs.
Graphene and lithium iron phosphate composite materials were prepared by Joule thermal synthesis technology, and improved Hummers method and rapid Joule heat treatment were used to obtain high-quality, low-defect graphene, and the uniformity and stability of the material were ensured through ball milling technology.
It improves the energy density and low-temperature performance of lithium iron phosphate batteries, reduces production costs, and enhances the conductive properties and cycling stability of the materials.
Smart Images

Figure CN119706814A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy lithium-ion battery material synthesis, and in particular to the preparation and application of a Joule heat-synthesized graphene and lithium iron phosphate composite material. Background Art
[0002] With the rapid development of the global economy, energy demand continues to grow. The traditional energy structure can no longer meet the needs of sustainable development, and the development and utilization of new energy has become the focus of global attention. In this context, lithium batteries, as an efficient and environmentally friendly energy storage device, play an important role in the field of new energy.
[0003] Among many lithium battery systems, lithium iron phosphate batteries have received extensive attention due to their high safety, environmental protection, and relatively low cost. The application of lithium iron phosphate batteries in batteries is mainly reflected in the following aspects: First, in the field of new energy vehicles, lithium iron phosphate batteries, as power batteries, provide reliable and lasting energy guarantees for electric vehicles; second, in the field of energy storage, lithium iron phosphate batteries have broad application prospects in peak load regulation and backup power supply; third, in portable electronic devices such as mobile phones and laptops, lithium iron phosphate batteries are used to a certain extent due to their safety performance.
[0004] However, lithium iron phosphate batteries also face some difficulties in their development. First, the energy density is low. Compared with ternary material batteries, lithium iron phosphate batteries have disadvantages in terms of endurance. Second, the low-temperature performance is poor, especially in cold northern regions, the discharge performance and charging speed of lithium iron phosphate batteries will be greatly affected. Third, the production cost is high. Although the cost of lithium iron phosphate batteries is relatively low, the preparation process is complicated and the energy consumption is high during the production process, resulting in the overall cost still has room for reduction. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the shortcomings of the prior art, the present invention provides a preparation and application of a Joule heat synthesized graphene and lithium iron phosphate composite material, which solves the problems of relatively low energy density of traditional lithium iron phosphate batteries and relatively low battery life compared with ternary lithium batteries.
[0007] (II) Technical solution
[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0009] A preparation method of a composite material of graphene and lithium iron phosphate synthesized by Joule heat, comprising the following steps:
[0010] S101. The product of natural graphite being subjected to acid treatment and heat treatment is a graphite precursor, and then ultra-large sheet diameter graphene oxide is obtained by an improved Hummers method;
[0011] S102. The ultra-large-diameter graphene oxide in step S101 is converted into a large-diameter low-defect graphene material by using high voltage, high heat and high pressure of rapid Joule heat;
[0012] Through the above technical scheme, by improving the combination of Hummers method and Joule heat treatment, high-quality, low-defect graphene with good electrical conductivity and stability can be obtained.
[0013] Furthermore, the graphite precursor is prepared according to the following steps:
[0014] Natural graphite and concentrated sulfuric acid were mixed and stirred, and then concentrated nitric acid was added and stirred at room temperature. Ultrapure water was then slowly poured into the mixture, and the obtained product was washed several times with ultrapure water, then centrifuged and dried at 60°C for 24h, and the dried powder was heat-treated at 1000°C to obtain a graphite precursor;
[0015] Further, the sulfuric acid concentration is 70-98% (Wt%), the nitric acid concentration is 86%-97.5% (Wt%), the volume ratio of the graphite mass to the concentrated sulfuric acid is 1:20-1:50, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 2:1-4:1, and the stirring time at room temperature is 18-36 hours;
[0016] Through the above technical solution, the degree of graphene oxidation can be controlled to ensure the quality and reaction efficiency of graphene oxidation. Too strong or too weak acidic conditions will affect the degree of oxidation and size. The optimized conditions can ensure that the graphene oxide has a suitable size, good dispersibility and suitable oxidation functional groups, which is conducive to subsequent processing and performance improvement of composite materials.
[0017] Furthermore, the heat treatment in step S101 is performed at a temperature of 800-1200° C. and for a time of 10-40 seconds;
[0018] Furthermore, the discharge time of the rapid Joule heat in step S102 is 100-800ms;
[0019] Furthermore, the rapid Joule heat in step S102 needs to be pre-processed, the pre-processed capacitor voltage is 80-250V, and the number of pre-processing times is 1-10 times;
[0020] Furthermore, in the step S102, the capacitor voltage of the rapid Joule heating is 100-300V, the current is 10-80A, and the number of discharges is 1-5 times;
[0021] Through the above technical scheme, by adjusting the parameters of Joule heat treatment such as voltage, current, and discharge time, the degree of reduction of graphene oxide and the defect density of the material can be accurately controlled. This can make the final graphene material have good conductivity and stable structure, and provide ideal electrochemical properties and mechanical properties for the composite material. The optimized Joule heat treatment can also reduce the heat loss and time consumption that may occur in the production process, thereby improving production efficiency.
[0022] Furthermore, in step S103, the ball milling time is 1-6 hours, the ball milling speed is 200-600 rpm / min, and the ball-to-material ratio of the ball milling is 2:1-1:1;
[0023] Through the above technical solution, the optimization of the ball milling process can ensure the full contact and uniform dispersion of graphene and lithium iron phosphate. The appropriate ball milling time and speed can avoid excessive wear or agglomeration of the material and ensure the uniformity and stability of the composite material. The ball milling process not only helps to improve the conductivity of the composite material, but also improves the cycle stability and service life of the material.
[0024] Furthermore, a graphene and lithium iron phosphate composite material prepared by the rapid Joule heating method according to any of the above items is used as an electrode in an ion battery.
[0025] (III) Beneficial effects
[0026] The present invention provides a preparation and application of a composite material of graphene and lithium iron phosphate synthesized by Joule heat. It has the following beneficial effects:
[0027] 1. The present invention provides a preparation and application of a Joule heat synthesized graphene and lithium iron phosphate composite material. At the material level, the performance of the lithium iron phosphate battery is improved by means of doping, coating, etc. In terms of structural design, new electrode materials are used and the battery structure is optimized to improve energy density and low-temperature performance. In terms of preparation technology, a green and low-cost preparation method is developed to reduce production costs.
[0028] 2. The present invention provides a preparation and application of Joule thermal synthesis of graphene and lithium iron phosphate composite materials. Joule thermal synthesis has attracted much attention in the preparation of new energy battery materials because electric current is directly converted into thermal energy without the need for an external heat source. It simplifies the high-temperature synthesis process and improves the purity and performance of materials. Especially in the preparation of battery positive electrode materials, Joule thermal synthesis promotes the improvement of battery energy density and stability, providing a new way for innovation in new energy battery technology.
[0029] 3. The present invention provides the preparation and application of a composite material of graphene and lithium iron phosphate synthesized by Joule heat. The Joule heat treatment quickly heats the graphene oxide through electric current, and can efficiently reduce its oxidized groups in a short time, while reducing the damage to the material structure caused by high-temperature treatment. At the same time, the graphene can be reduced quickly and energy-savingly, and the degree of reduction can be accurately controlled to avoid excessive reduction or structural damage that may occur in traditional reduction methods. The composite of ball-milled graphene and lithium iron phosphate can achieve uniform distribution of graphene on the surface of lithium iron phosphate particles, thereby improving the electronic conductivity and stability of lithium iron phosphate batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a flow chart of the steps of the present invention;
[0031] Figure 2 This is a SEM electron microscope image of graphene of the present invention;
[0032] Figure 3 is the XRD spectrum of graphene of the present invention;
[0033] Figure 4 The XRD spectrum of the large-diameter low-defect graphene and lithium iron phosphate composite material of the present invention;
[0034] Figure 5 This is a performance comparison chart of the large-diameter, low-defect graphene and lithium iron phosphate composite materials of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] 3 g of natural graphite and 100 mL of 95% concentrated sulfuric acid were mixed and stirred, and 30 mL of 95% concentrated nitric acid was added to the mixture, and stirred at room temperature for 24 hours. Ultrapure water was slowly added to the mixture, and then washed with ultrapure water 5 times, centrifuged, and dried at 60°C overnight. The obtained powder was heated at 1000°C for 20 seconds to obtain a graphite precursor.
[0038] Then, the obtained graphite precursor was used to prepare ultra-large-diameter graphene by a modified Hummers method: 2g of graphite precursor and 60mL of concentrated sulfuric acid were stirred and mixed for 5min, and 10g of KMnO4 was added to the mixture and stirred and mixed for 15min. Then it was placed in a constant temperature water bath at 45°C for 1h to obtain a dark brown solution. The solution was transferred to an ice bath, and 200mL of deionized water and 50mL of 30% H2O2 (Wt%) were slowly added to the mixture, and the color of the solution changed to light brown.
[0039] The GO particles were washed with HCl solution and deionized water until the pH value of the solution became 6-7. The obtained product was centrifuged and dried at 90°C overnight to obtain ultra-large-diameter graphene oxide powder.
[0040] Take a quartz tube with an inner diameter of 8mm and a length of 70mm, install a conductive plug at one end, load ultra-large-diameter graphene oxide powder from the other end, and then install another conductive plug to form a relatively closed reaction tube. The capacitor group consists of 5 capacitors; before the reaction, it is vacuumed to reduce the air pressure to 0.02MPA, and then the capacitor group is charged with a DC power supply. The parameters are set: pre-treatment capacitor voltage 50V, pre-treatment times 1 time, applied capacitor voltage 190V, and discharge times 1 time. After the reaction is completed, the device is quickly cooled to room temperature and ensure that the capacitor group is fully discharged. Subsequently, the product is collected.
[0041] The lithium iron phosphate powder and the collected product were placed in a ball mill at a mass ratio of 97:3, a ball-to-material ratio of 1:1, a ball mill speed of 300 rpm / min, and a ball milling time of 1 h. After ball milling, the product was collected. Figure 5 This is a performance comparison chart of large-diameter low-defect graphene and lithium iron phosphate composite materials. It can be clearly seen that the performance of large-diameter low-defect graphene and lithium iron phosphate composite materials has been greatly improved compared with ordinary lithium iron phosphate. The specific capacity has increased from the initial 147.68mAh / g to 157.67mAh / g. Even after 350 cycles, compared with the ordinary lithium iron phosphate 141.48mAh / g, it still shows a specific capacity of 151.17mAh / g, showing excellent cycle stability. Figure 4 It is the XRD spectrum of large-diameter low-defect graphene and lithium iron phosphate composite material. Its characteristic peaks are consistent with lithium iron phosphate, and the characteristic peak of graphene (002) appears near 27°.
[0042] Embodiment 2:
[0043] The process of Example 1 was used to prepare the graphite precursor, but the amount of 95% concentrated sulfuric acid was changed to 60 mL, the amount of 95% concentrated nitric acid was changed to 15 mL, and the stirring time at room temperature was changed to 36 h. Thus, graphite precursors prepared under different conditions were obtained.
[0044] The precursor is collected, and graphene is prepared from the material according to the process method of Example 1, and then compounded with ordinary lithium iron phosphate, that is, graphene and lithium iron phosphate composite materials under different conditions are obtained.
[0045] Embodiment 3:
[0046] Using the process of Example 1, in the preparation process of the graphite precursor, 3g of natural graphite and 100mL of concentrated sulfuric acid with a concentration of 70% were mixed and stirred, and 30mL of concentrated nitric acid with a concentration of 86% was added to the mixture, and stirred at room temperature for 24 hours. Ultrapure water was slowly added to the mixture, and then washed with ultrapure water 5 times, centrifuged, and dried at 60°C overnight. The obtained powder was heated at 800°C for 25 seconds to obtain a graphite precursor. That is, graphite precursors prepared under different conditions were obtained.
[0047] The precursor is collected, and graphene is prepared from the material according to the process method of Example 1, and then compounded with ordinary lithium iron phosphate, that is, graphene and lithium iron phosphate composite materials under different conditions are obtained.
[0048] Embodiment 4:
[0049] The process method of Example 1 was used, and the number of capacitors in the capacitor group was switched to one during the rapid Joule heat treatment, and the parameters were adjusted: pretreatment capacitor voltage 50V, pretreatment times 1 time, applied capacitor voltage 150V, and discharge times 6 times. Subsequently, the product was collected.
[0050] That is, corresponding graphene materials under different rapid Joule thermal voltages are obtained. The material is compounded with ordinary lithium iron phosphate according to the process method of Example 1, that is, graphene and lithium iron phosphate composite materials under different conditions are obtained.
[0051] Embodiment 5:
[0052] The process method of Example 1 was used, and the parameters were adjusted during the rapid Joule heat treatment process: pretreatment capacitor voltage 80V, pretreatment times 5 times, applied capacitor voltage 120V, discharge times 2 times. Subsequently, the product was collected.
[0053] The corresponding graphene materials under different rapid Joule thermal voltages are obtained. The material is compounded with ordinary lithium iron phosphate according to the process method of Example 1, and the ball milling parameters are changed to: ball-to-material ratio is 1.5:1, ball mill speed is 200 rpm / min, and ball milling time is 1h, so that graphene and lithium iron phosphate composite materials under different conditions are obtained.
[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation method of a composite material of graphene and lithium iron phosphate synthesized by Joule heat, characterized in that: The following steps are included: S101. The product of natural graphite being subjected to acid treatment and heat treatment is a graphite precursor, and then ultra-large sheet diameter graphene oxide is obtained by an improved Hummers method; S102. The ultra-large-diameter graphene oxide in step S101 is converted into a large-diameter low-defect graphene material by using high voltage, high heat and high pressure of rapid Joule heat; S103. The graphene material and lithium iron phosphate powder in step S102 are transferred into a ball mill for ball milling to finally obtain a composite material.
2. The preparation of a composite material of graphene and lithium iron phosphate synthesized by Joule heat according to claim 1, characterized in that: The graphite precursor is prepared according to the following steps: Natural graphite and concentrated sulfuric acid are mixed and stirred, and then concentrated nitric acid is added and stirred at room temperature. Ultrapure water is then slowly poured into the mixture, and the resulting product is washed multiple times with ultrapure water, then centrifuged and dried at 60°C for 24 hours, and the dried powder is heat-treated at 1000°C to obtain a graphite precursor.
3. The preparation of a Joule heat synthesized graphene and lithium iron phosphate composite material according to claim 2, characterized in that: The sulfuric acid concentration is 70-98% (Wt%), the nitric acid concentration is 86%-97.5% (Wt%), the volume ratio of graphite mass to concentrated sulfuric acid is 1:20-1:50, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 2:1-4:1, and the stirring time at room temperature is 18-36 hours.
4. The preparation of a composite material of graphene and lithium iron phosphate synthesized by Joule heat according to claim 1, characterized in that: The heat treatment in step S101 is performed at a temperature of 800-1200° C. and for a time of 10-40 seconds.
5. The preparation of a Joule heat synthesized graphene and lithium iron phosphate composite material according to claim 1, characterized in that: The discharge time of the rapid Joule heat in step S102 is 100-800 ms.
6. The preparation of a Joule heat synthesized graphene and lithium iron phosphate composite material according to claim 1, characterized in that: The rapid Joule heat in step S102 needs to be pre-processed, the pre-processed capacitor voltage is 80-250V, and the number of pre-processing times is 1-10 times.
7. The preparation of a composite material of graphene and lithium iron phosphate synthesized by Joule heat according to claim 1, characterized in that: In the step S102, the capacitor voltage of the rapid Joule heating is 100-300V, the current is 10-80A, and the number of discharges is 1-5 times.
8. The preparation of a Joule heat synthesized graphene and lithium iron phosphate composite material according to claim 1, characterized in that: In the step S103, the ball milling time is 1-6 hours, the ball milling speed is 200-600 rpm / min, and the ball-to-material ratio of the ball milling is 2:1-1:
1.
9. Use of a graphene and lithium iron phosphate composite material prepared by a rapid Joule heating method according to any one of claims 1 to 8 as an electrode in an ion battery.
Citation Information
Patent Citations
Fabrication method of superlinearity resistance-changing reduced graphene oxide stress sensor
CN110186599A
Device and method for reducing graphene oxide
CN113003567A
Method for preparing doped graphene through rapid Joule heat and doped graphene
CN116354341A
High-entropy alloy composite material and Joule thermal preparation method and application thereof
CN118186463A
Synthesis of Ultra-Large Graphene Oxide Sheets
US20150071844A1